A Mathematica-based CAL matrix-theory tutor for scientists and engineers - M. A. Kelmanson; S. B. Maunders; S. Y. Cheng (Association for Learning Technology, 1993)
Under the TLTP initiative, the Mathematics Departments at Imperial College and Leeds University are jointly developing a CAL method directed at supplementing the level of mathematics of students entering science and engineering courses from diverse A-level (or equivalent) backgrounds. The aim of the joint project is to maintain - even increase - the number of students enrolling on such first-year courses without lowering the courses' existing mathematical standards. A CAL tutor for matrix theory is presented in this paper, in the form of Mathematica Notebooks. This constitutes one of a list of specific A-level mathematics core options required by science and engineering departments. The module has been written so as to recognize students' errors and advise accordingly. Questions are generated randomly, at run time, in order to preclude copying between users. The module incorporates automated performance indicators so as to impinge minimally on existing staff resources. As an aid to other CAL authors considering the use of Mathematica Notebooks, idiosyncratic difficulties encountered within Mathematica Notebooks are catalogued and discussed in detail.